Efisiensi Pengumpulan dan Pendistribusian Dana Zakat : (Studi Kasus Pada Baznas Kota Medan Tahun 2018-2022) - Khairul Faiz Batubara; Yenni Samri Juliati Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by the efficiency of collecting and distributing zakat which has not been maximized. The targets in question include solving poverty problems, income distribution, and improving the welfare of the people and the state. This shows how important zakat is as one of the pillars of Islam. The method used in this study is qualitative descriptive research, namely by reviewing literature and conducting data analysis, studying literature from various sources of books, the internet, and also research journals that have the same topic as the researcher mentioned. The results of the study conclude that the Zakat Collection Strategy can be interpreted as an activity to collect funds and other resources from the community (either individuals, groups, organizations, companies or the government) which will be used to finance the institution's programs and operational activities in the end is to achieve the mission and goals of the institution in the field of distribution including the fields of Economy, Education, Da'wah, Health, Social and Humanitarian. It is evidenced by the collection and distribution/distribution of zakat funds carried out by the Medan City Baznas experiencing a positive trend from year to year which is quite significant, having an impact on the performance of the Medan City Baznas to continue to increase and of course with public awareness to distribute zakat through official institutions is getting higher so that justice and welfare are created in kaffah.